Atomic defect classification of the H–Si(100) surface through multi-mode scanning probe microscopy - Croshaw, Jeremiah; Dienel, Thomas; Huff, Taleana; Wolkow, Robert (Beilstein Journal of Nanotechnology, 2020)
The combination of scanning tunnelling microscopy (STM) and non-contact atomic force microscopy (nc-AFM) allows enhanced extraction and correlation of properties not readily available via a single imaging mode. We demonstrate this through the characterization and classification of several commonly found defects of the hydrogen-terminated silicon (100)-2 × 1 surface (H–Si(100)-2 × 1) by using six unique imaging modes. The H–Si surface was chosen as it provides a promising platform for the development of atom scale devices, with recent work showing their creation through precise desorption or placement of surface hydrogen atoms. While samples with relatively large areas of the H–Si surface are routinely created using an in situ methodology, surface defects are inevitably formed reducing the area available for patterning. By probing the surface using the different interactivity afforded by either hydrogen- or silicon-terminated tips, we are able to extract new insights regarding the atomic and electronic structure of these defects. This allows for the confirmation of literature assignments of several commonly found defects, as well as proposed classifications of previously unreported and unassigned defects. By combining insights from multiple imaging modes, better understanding of their successes and shortcomings in identifying defect structures and origins is achieved. With this, we take the first steps toward enabling the creation of superior H–Si surfaces through an improved understanding of surface defects, ultimately leading to more consistent and reliable fabrication of atom scale devices.
Keywords: atomic force microscopy; hydrogen-terminated silicon; scanning tunnelling hydrogen microscopy; scanning tunnelling microscopy; surface metrology

IEEE International Electron Devices Meeting - Prati, E.; Shinada, T. (Atomic scale devices: Advancements and directions, San Francisco, CA, USA, 15.12.2014-17.12.2014)

(untitled) - O’Brien, J. L.; Schofield, S. R.; Simmons, M. Y.; Clark, R. G.; Dzurak, A. S.; Curson, N. J.; Kane, B. E.; McAlpine, N. S.; Hawley, M. E.; Brown, G. W. (Phys. Rev. B, 2001)

(untitled) - He, Y.; Gorman, S. K.; Keith, D.; Kranz, L.; Keizer, J. G.; Simmons, M. Y. (Nature, 2019)

(untitled) - Fuechsle, M.; Miwa, J. A.; Mahapatra, S.; Ryu, H.; Lee, S.; Warschkow, O.; Hollenberg, L. C. L.; Klimeck, G.; Simmons, M. Y. (Nat. Nanotechnol., 2012)

(untitled) - Wyrick, J.; Wang, X.; Kashid, R. V.; Namboodiri, P.; Schmucker, S. W.; Hagmann, J. A.; Liu, K.; Stewart, M. D., Jr; Richter, C. A.; Bryant, G. W.; Silver, R. M. (Adv. Funct. Mater., 2019)

(untitled) - Huff, T.; Labidi, H.; Rashidi, M.; Livadaru, L.; Dienel, T.; Achal, R.; Vine, W.; Pitters, J.; Wolkow, R. A. (Nat. Electron., 2018)

(untitled) - Yengui, M.; Duverger, E.; Sonnet, P.; Riedel, D. (Nat. Commun., 2017)

(untitled) - Kolmer, M.; Zuzak, R.; Dridi, G.; Godlewski, S.; Joachim, C.; Szymonski, M. (Nanoscale, 2015)

(untitled) - Huff, T. R.; Dienel, T.; Rashidi, M.; Achal, R.; Livadaru, L.; Croshaw, J.; Wolkow, R. A. (ACS Nano, 2019)

(untitled) - Rashidi, M.; Croshaw, J.; Mastel, K.; Tamura, M.; Hosseinzadeh, H.; Wolkow, R. A. (Mach. Learn.: Sci. Technol., 2020)

(untitled) - Gordon, O.; D’Hondt, P.; Knijff, L.; Freeney, S. E.; Junqueira, F.; Moriarty, P.; Swart, I. (Rev. Sci. Instrum., 2019)

(untitled) - Ziatdinov, M.; Fuchs, U.; Owen, J. H. G.; Randall, J. N.; Kalinin, S. V. (arXiv, 2020)
https://arxiv.org/abs/2002.04716

(untitled) - Chadi, D. J. (Phys. Rev. Lett., 1979)

(untitled) - Hamers, R. J.; Köhler, U. K. (J. Vac. Sci. Technol., A, 1989)

(untitled) - Hossain, M. Z.; Yamashita, Y.; Mukai, K.; Yoshinobu, J. (Phys. Rev. B, 2003)

(untitled) - Yu, S.-Y.; Kim, H.; Koo, J.-Y. (Phys. Rev. Lett., 2008)

(untitled) - Sobotík, P.; Ošt’ádal, I. (Surf. Sci., 2008)

(untitled) - Sweetman, A.; Danza, R.; Gangopadhyay, S.; Moriarty, P. (J. Phys.: Condens. Matter, 2012)

(untitled) - Boland, J. J. (Phys. Rev. Lett., 1990)

(untitled) - Boland, J. J. (Adv. Phys., 1993)

(untitled) - Boland, J. J. (Surf. Sci., 1992)

(untitled) - Hamers, R. J.; Wang, Y. (Chem. Rev., 1996)

(untitled) - Hapala, P.; Kichin, G.; Wagner, C.; Tautz, F. S.; Temirov, R.; Jelínek, P. (Phys. Rev. B: Condens. Matter Mater. Phys., 2014)

Probe Particle Model - Hapala, P. (2014)

(untitled) - Møller, M.; Jarvis, S. P.; Guérinet, L.; Sharp, P.; Woolley, R.; Rahe, P.; Moriarty, P. (Nanotechnology, 2017)

(untitled) - Huff, T. R.; Labidi, H.; Rashidi, M.; Koleini, M.; Achal, R.; Salomons, M. H.; Wolkow, R. A. (ACS Nano, 2017)

(untitled) - Kuzmin, M.; Mäkelä, J.; Lehtiö, J.; Yasir, M.; Tuominen, M.; Rad, Z. S. J.; Lahti, A.; Punkkinen, M. P. J.; Laukkanen, P.; Kokko, K. (Phys. Rev. B, 2018)

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Liljeroth, P.; Meyer, G. (Science, 2009)

(untitled) - Mönig, H.; Todorović, M.; Baykara, M. Z.; Schwendemann, T. C.; Rodrigo, L.; Altman, E. I.; Pérez, R.; Schwarz, U. D. (ACS Nano, 2013)

(untitled) - Mönig, H.; Amirjalayer, S.; Timmer, A.; Hu, Z.; Liu, L.; Díaz Arado, O.; Cnudde, M.; Strassert, C. A.; Ji, W.; Rohlfing, M.; Fuchs, H. (Nat. Nanotechnol., 2018)

(untitled) - Mohn, F.; Schuler, B.; Gross, L.; Meyer, G. (Appl. Phys. Lett., 2013)

(untitled) - Kichin, G.; Weiss, C.; Wagner, C.; Tautz, F. S.; Temirov, R. (J. Am. Chem. Soc., 2011)

(untitled) - Temirov, R.; Soubatch, S.; Neucheva, O.; Lassise, A. C.; Tautz, F. S. (New J. Phys., 2008)

(untitled) - Simic-Milosevic, V.; Mehlhorn, M.; Morgenstern, K. (ChemPhysChem, 2016)

(untitled) - Weiss, C.; Wagner, C.; Kleimann, C.; Rohlfing, M.; Tautz, F. S.; Temirov, R. (Phys. Rev. Lett., 2010)

(untitled) - Achal, R.; Rashidi, M.; Croshaw, J.; Churchill, D.; Taucer, M.; Huff, T.; Cloutier, M.; Pitters, J.; Wolkow, R. A. (Nat. Commun., 2018)

(untitled) - Martínez, J. I.; Abad, E.; González, C.; Flores, F.; Ortega, J. (Phys. Rev. Lett., 2012)

(untitled) - Sharp, P.; Jarvis, S.; Woolley, R.; Sweetman, A.; Kantorovich, L.; Pakes, C.; Moriarty, P. (Appl. Phys. Lett., 2012)

(untitled) - Pérez, R.; Payne, M. C.; Štich, I.; Terakura, K. (Phys. Rev. Lett., 1997)

(untitled) - Pavliček, N.; Majzik, Z.; Meyer, G.; Gross, L. (Appl. Phys. Lett., 2017)

(untitled) - Welker, J.; Weymouth, A. J.; Giessibl, F. J. (ACS Nano, 2013)

(untitled) - Sugimoto, Y.; Onoda, J. (Appl. Phys. Lett., 2019)

(untitled) - Labidi, H.; Koleini, M.; Huff, T.; Salomons, M.; Cloutier, M.; Pitters, J.; Wolkow, R. A. (Nat. Commun., 2017)

(untitled) - Sang, H.; Jarvis, S. P.; Zhou, Z.; Sharp, P.; Moriarty, P.; Wang, J.; Wang, Y.; Kantorovich, L. (Sci. Rep., 2014)

(untitled) - Foster, A. S.; Gal, A. Y.; Gale, J. D.; Lee, Y. J.; Nieminen, R. M.; Shluger, A. L. (Phys. Rev. Lett., 2004)

(untitled) - Hata, K.; Yoshida, S.; Shigekawa, H. (Phys. Rev. Lett., 2002)

(untitled) - Sagisaka, K.; Fujita, D.; Kido, G. (Phys. Rev. Lett., 2003)

(untitled) - Wolkow, R. A. (Phys. Rev. Lett., 1992)

(untitled) - Shigekawa, H.; Miyake, K.; Ishida, M.; Ozawa, S.; Hata, K. (Defect Diffus. Forum, 1998)

(untitled) - Bellec, A.; Riedel, D.; Dujardin, G.; Boudrioua, O.; Chaput, L.; Stauffer, L.; Sonnet, P. (Phys. Rev. B, 2009)

(untitled) - Engelund, M.; Godlewski, S.; Kolmer, M.; Zuzak, R.; Such, B.; Frederiksen, T.; Szymonski, M.; Sánchez-Portal, D. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Lyding, J. W.; Shen, T.-C.; Abeln, G. C.; Wang, C.; Tucker, J. R. (Nanotechnology, 1996)

(untitled) - Schofield, S. R.; Studer, P.; Hirjibehedin, C. F.; Curson, N. J.; Aeppli, G.; Bowler, D. R. (Nat. Commun., 2013)

(untitled) - Taucer, M.; Livadaru, L.; Piva, P. G.; Achal, R.; Labidi, H.; Pitters, J. L.; Wolkow, R. A. (Phys. Rev. Lett., 2014)

(untitled) - Labidi, H.; Taucer, M.; Rashidi, M.; Koleini, M.; Livadaru, L.; Pitters, J.; Cloutier, M.; Salomons, M.; Wolkow, R. A. (New J. Phys., 2015)

(untitled) - Campbellová, A.; Ondráček, M.; Pou, P.; Pérez, R.; Klapetek, P.; Jelínek, P. (Nanotechnology, 2011)

(untitled) - Pou, P.; Ghasemi, S. A.; Jelinek, P.; Lenosky, T.; Goedecker, S.; Perez, R. (Nanotechnology, 2009)

(untitled) - Sinthiptharakoon, K.; Schofield, S. R.; Studer, P.; Brázdová, V.; Hirjibehedin, C. F.; Bowler, D. R.; Curson, N. J. (J. Phys.: Condens. Matter, 2014)

(untitled) - Liu, L.; Yu, J.; Lyding, J. W. (IEEE Trans. Nanotechnol., 2002)

(untitled) - Liu, L.; Yu, J.; Lyding, J. W. (Appl. Phys. Lett., 2001)

(untitled) - Domke, C.; Ebert, P.; Heinrich, M.; Urban, K. (Phys. Rev. B, 1996)

(untitled) - Lee, D. H.; Gupta, J. A. (Science, 2010)

(untitled) - Ebert, P.; Heinrich, M.; Simon, M.; Domke, C.; Urban, K.; Shih, C. K.; Webb, M. B.; Lagally, M. G. (Phys. Rev. B, 1996)

(untitled) - Kajiyama, H.; Suwa, Y.; Heike, S.; Fujimori, M.; Nara, J.; Ohno, T.; Matsuura, S.; Hitosugi, T.; Hashizume, T. (J. Phys. Soc. Jpn., 2005)

(untitled) - Wang, C.; Zhang, Y.; Jia, Y. (Solid State Sci., 2009)

(untitled) - Bellec, A.; Riedel, D.; Dujardin, G.; Rompotis, N.; Kantorovich, L. N. (Phys. Rev. B, 2008)

(untitled) - Suwa, Y.; Fujimori, M.; Heike, S.; Terada, Y.; Yoshimoto, Y.; Akagi, K.; Sugino, O.; Hashizume, T. (Jpn. J. Appl. Phys., Part 1, 2006)

(untitled) - Suwa, Y.; Fujimori, M.; Heike, S.; Terada, Y.; Yoshimoto, Y.; Akagi, K.; Sugino, O.; Hashizume, T. (Phys. Rev. B, 2006)

(untitled) - Suwa, Y.; Matsuura, S.; Fujimori, M.; Heike, S.; Onogi, T.; Kajiyama, H.; Hitosugi, T.; Kitazawa, K.; Uda, T.; Hashizume, T. (Phys. Rev. Lett., 2003)

(untitled) - Cheng, C. C.; Yates, J. T. (Phys. Rev. B, 1991)

(untitled) - Chen, D.; Boland, J. J. (Surf. Sci., 2002)

(untitled) - Weakliem, P. C.; Zhang, Z.; Metiu, H. (Surf. Sci., 1995)

(untitled) - Owen, J. H. G.; Bowler, D. R.; Goringe, C. M.; Miki, K.; Briggs, G. A. D. (Surf. Sci., 1995)

Noncontact Atomic Force Microscopy - Morita, S.; Wiesendanger, R.; Meyer, E. (Springer, 2002)

(untitled) - Chabal, Y. J.; Raghavachari, K. (Phys. Rev. Lett., 1985)

(untitled) - Maeng, J. Y.; Kim, S.; Jo, S. K.; Fitts, W. P.; White, J. M. (Appl. Phys. Lett., 2001)

(untitled) - Buehler, E. J.; Boland, J. J. (Surf. Sci., 1999)

(untitled) - Hitosugi, T.; Suwa, Y.; Matsuura, S.; Heike, S.; Onogi, T.; Watanabe, S.; Hasegawa, T.; Kitazawa, K.; Hashizume, T. (Phys. Rev. Lett., 1999)

(untitled) - Ballard, J. B.; Owen, J. H. G.; Alexander, J. D.; Owen, W. R.; Fuchs, E.; Randall, J. N.; Longo, R. C.; Cho, K. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2014)

(untitled) - Trenhaile, B. R.; Agrawal, A.; Weaver, J. H. (Appl. Phys. Lett., 2006)

(untitled) - Avouris, P.; Cahill, D. (Ultramicroscopy, 1992)

(untitled) - Roberson, M. A.; Estreicher, S. K. (Phys. Rev. B, 1994)

(untitled) - Xu, H. (Phys. Rev. B, 1992)

(untitled) - Zundel, T.; Weber, J. (Phys. Rev. B, 1992)

(untitled) - Herrero, C. P.; Stutzmann, M.; Breitschwerdt, A. (Phys. Rev. B, 1991)

(untitled) - Ong, C. K.; Khoo, G. S. (J. Phys.: Condens. Matter, 1991)

(untitled) - Rizk, R.; de Mierry, P.; Song, C.; Ballutaud, D.; Pajot, B. (J. Appl. Phys., 1991)

(untitled) - Giessibl, F. J. (Appl. Phys. Lett., 1998)

(untitled) - Giessibl, F. J. (Rev. Sci. Instrum., 2019)

(untitled) - Rezeq, M.; Pitters, J.; Wolkow, R. (J. Chem. Phys., 2006)

(untitled) - Labidi, H.; Kupsta, M.; Huff, T.; Salomons, M.; Vick, D.; Taucer, M.; Pitters, J.; Wolkow, R. A. (Ultramicroscopy, 2015)

(untitled) - Rashidi, M.; Wolkow, R. A. (ACS Nano, 2018)

(untitled) - Pitters, J. L.; Piva, P. G.; Wolkow, R. A. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2012)

Avogadro: An Open-Source Molecular Builder and Visualization Tool (Avogadro Chemistry)

(untitled) - Hanwell, M. D.; Curtis, D. E.; Lonie, D. C.; Vandermeersch, T.; Zurek, E.; Hutchison, G. R. (J. Cheminf., 2012)

(untitled) - Halgren, T. A. (J. Comput. Chem., 1996)

(untitled) - Macrae, C. F.; Bruno, I. J.; Chisholm, J. A.; Edgington, P. R.; McCabe, P.; Pidcock, E.; Rodriguez-Monge, L.; Taylor, R.; van de Streek, J.; Wood, P. A. (J. Appl. Crystallogr., 2008)